Association between rs2787094 Genetic Variants in ADAM33 Gene and Asthma in Indonesian Population: Preliminary study - Viyati, Kencono; Prayuni, Kinasih; Zulhamidah, Yenni; Razari, Intan; Yuliwulandari, Rika (UI Scholars Hub, 2023)
Background: Asthma is a multifactorial disease that encompasses a multitude of genetic and environmental factors. One such factor is the disintegrin and metalloprotein-33 (ADAM33) gene, which is correlated with asthma and bronchial hyperresponsiveness. Previous studies conducted on Asian populations have reported a significant association between rs2787094 polymorphism in the ADAM33 gene and asthma. Methods: Our study involved 153 Indonesian participants. TaqMan genotyping assay was used to analyze rs2787094 polymorphism in the ADAM33 gene. Results: No significant association was detected between the allele and genotype frequencies of rs2787094 and asthma in the case and control subjects (p = 1.00). The distribution of rs2787094 genotypes in healthy controls was CC (12.1%), CG (42.1%), and GG (45.8%). The genotype distribution in Indonesians was similar to East Asians in 1,000 genomes dataset. Conclusions: This is the first study to investigate the association between rs2787094 polymorphism in the ADAM33 gene and asthma in the Indonesian population and concluded that it is not associated. Future studies with larger sample sizes and more single nucleotide polymorphisms in the ADAM33 gene are needed to validate these results.